Determinants Influencing the Adoption of Rice Intensification System among Smallholders in Mwea Irrigation Scheme, Kenya - Francis Kadipo Kaloi; Hezron Nyarindo Isaboke; Charles Nyambane Onyari; Lucy Karega Njeru (Advances in Agriculture)
Rice farming has received considerable attention in developing countries and particularly in Kenya due to its impact on smallholders’ income and food security. Irrigated rice is the largest consumer of water, and its sustainability is threatened by water shortage. This has necessitated the development of alternative irrigation water technologies, such as the system of rice intensification (SRI), which are efficient in water use with improved yields. This study analyzed the determinants of adoption of SRI in the Mwea Irrigation Scheme where stratified sampling was used to obtain 364 smallholder rice farmers. A semistructured questionnaire was used to collect primary data, which was then analyzed using a binary logistic regression model. The results showed that age (−0.3%) was significant but with a negative effect on adoption of SRI. Farm size (2.499%), household size (1.895%), distance from the canal (1.354%), off-farm work (3.953%), access to credit services (8.714%), access to extension services (7.809%), and years in rice farming (0.409%) were found positively and significantly influencing factors to the adoption of SRI. Therefore, this study concludes that smallholders attempt to improve rice productivity through adoption of SRI should give a special priority to all significant factors.